Pendidikan Resiliensi Mental pada Anak yang Beribu Nenek (Studi Terhadap Tiga Nenek Sukses yang Mengasuh Cucu Kandungnya) - Rahmatullah, Azam Syukur; Chaer, Moh. Toriqul (MUWAZAH: Jurnal Kajian Gender, 2020)
This research aims to explore the way grandmother’s struggle hard in educating her grandchildren, who are entrusted to them by their biological parents. This research is field research with a phenomenological approach. The research location was in the Puring, Kebumen, Central Java, with three grandmothers who are considered successful in raising and educating their biological grandchildren. The three grandmothers were taken into a sample based on appropriate criteria and were deemed to be successful in applying mental resilience education to their biological grandchildren. Grandchildren who are used as objects of research are also those who are considered successful in implementing mental resilience education imposed by their grandmothers. The findings of this study stated that from these three grandmothers in Puring Kebumen, all of them had concepts and actions that were appropriate and clear to be applied to their grandchildren. Children who grandmothers raise have good cognitive and independent development. The relationship between grandmother, mother and child show a synergy for emotional attachment between them. The significance of the younger mother, the length of education, and the grandmother's attachment will affect the increased independence of the child.